2010
DOI: 10.1002/hep.23908
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis C virus replication using adeno-associated virus vector delivery of an exogenous anti-hepatitis C virus microrna cluster

Abstract: RNA interference (RNAi) is being evaluated as an alternative therapeutic strategy for hepatitis C virus (HCV) infection. The use of viral vectors encoding short hairpin RNAs (shRNAs) has been the most common strategy employed to provide sustained expression of RNAi effectors. However, overexpression and incomplete processing of shRNAs has led to saturation of the endogenous miRNA pathway, resulting in toxicity. The use of endogenous microRNAs (miRNAs) as scaffolds for short interfering (siRNAs) may avoid these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…The human mir-17-92 cluster on chromosome 13, which encodes a 1 kb pri-miRNA polycistronic transcript that produces seven mature miRNAs, was modi fi ed to encode up to four embedded shRNA sequences, leading to effective HIV inhibition ( 96 ) . Similar studies have used the chicken miR-126 cluster to express shRNAs targeting in fl uenza ( 97 ) , the human mir106b-mir93-mir2548 cluster to express anti-HIV molecules ( 149 ) , and fi ve of the miRNAs from the miRNA-17-92 cluster were modi fi ed to target different regions of the HCV genome ( 150 ) .…”
Section: Combinatorialrnaimentioning
confidence: 98%
“…The human mir-17-92 cluster on chromosome 13, which encodes a 1 kb pri-miRNA polycistronic transcript that produces seven mature miRNAs, was modi fi ed to encode up to four embedded shRNA sequences, leading to effective HIV inhibition ( 96 ) . Similar studies have used the chicken miR-126 cluster to express shRNAs targeting in fl uenza ( 97 ) , the human mir106b-mir93-mir2548 cluster to express anti-HIV molecules ( 149 ) , and fi ve of the miRNAs from the miRNA-17-92 cluster were modi fi ed to target different regions of the HCV genome ( 150 ) .…”
Section: Combinatorialrnaimentioning
confidence: 98%
“…To address the issue HCV-infected cells were transduced with a lentiviral vector and we observed effective viral inhibition for both single and dual shRNA (Fig.7a-d, 8a, b). Few contemporary studies have also shown similar synergistic effects on HCV inhibition upon transduction with multiple shRNA expressing adenoviral or adeno-associated viral vectors [14,15,27,28].…”
Section: Discussionmentioning
confidence: 95%
“…HCV often causes chronic infections and, therefore, a consistent presence of effective doses of siRNA would be DOI: 10.1159/000492220 obligatory for a sustained virological response (SVR), which is feasible either by frequent deliveries of exogenous siRNA or in vivo expression of shRNA [13,14]. However, repetitive administration of exogenous siRNA may not be feasible in the clinical setting; therefore, approaches for in vivo expression of shRNAs have been evaluated [15,16]. Lentiviral vectors derived from retroviruses are an attractive delivery option for stable expression of shRNA due to their ability to transduce many cell types, including dividing and nondividing cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the authors suggested the potential of their system as a promising alternative to the existing anti-HCV treatments. 147 RNAi based anti-viral HBV therapeutic approach for viral and cellular targeting shown in Figure 7.…”
Section: Viral-vector Based Delivery Systems For Hbvmentioning
confidence: 99%